Does Digital Transformation Stimulate the Unemployment Rate in Vietnam? - Liệu, Phan Thị; Hiếu Nguyễn Văn; Nhật Trần Hồng (Journal of Reviews on Global Economics, 2022)
Digital transformation is a significant driver for better economic growth. However, it might lead to massive changes in the economy’s structure. So, the impact of digital transformation on the unemployment rate is an interesting topic, especially in emerging countries. In Vietnam, the relationship between digital transformation and unemployment has not been explored. By adopting the cointegration test, and autoregressive distributed lag approach, our results reveal a negative impact of digital transformation on the unemployment rate in the long term. Besides, the outcome also indicates that inflation negatively influences unemployment both in the short- and long-run. This demonstrates that maintaining a certain inflation rate and boosting investments in digital transformation will be two key elements in keeping unemployment under control in this nation. This discovery contributes to the development of recommendations for lowering Vietnam’s unemployment rate.